2018
DOI: 10.17977/um002v10i12018p088
|View full text |Cite
|
Sign up to set email alerts
|

Import Components and Import Multipliers in Indonesian Economy: World Input-Output Analysis

Abstract: This paper calculates, presents and discusses on import components and the impact of final demand change on Indonesian imports using Indonesian 36 sector input-output tables of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Selain dalam lingkup nasional, keterkaitan antar wilayah juga dapat dilakukan dalam lingkup lebih luas. Muchdie et al (2018;2020) menggunakan tabel IO dunia untuk melihat keterkaitan spasial di enam negara asia dan menganlisis impor Indonesia. Dalam lingkup yang lebih sempit, tabel IO dapat digunakan untuk menganalisis lebih dalam misalkan analisis dampak pada sektor tertentu.…”
Section: Penelitian Sebelumnyaunclassified
“…Selain dalam lingkup nasional, keterkaitan antar wilayah juga dapat dilakukan dalam lingkup lebih luas. Muchdie et al (2018;2020) menggunakan tabel IO dunia untuk melihat keterkaitan spasial di enam negara asia dan menganlisis impor Indonesia. Dalam lingkup yang lebih sempit, tabel IO dapat digunakan untuk menganalisis lebih dalam misalkan analisis dampak pada sektor tertentu.…”
Section: Penelitian Sebelumnyaunclassified
“…40-54;Miller and Blair, 2009, pp. 3, 13;Sancho, 2012Sancho, , 2013Escaith, 2014;Okamoto, 2014;Soklis, 2014;Aroche Reyes and Marquez Mendoza, 2015;Jahn, 2015;Kelly, 2015;Imansyah et al, 2017;Muchdie et al, 2018;Trinh and Thai, 2021).…”
Section: The Problem's Statementmentioning
confidence: 99%
“…This matrices have been used either for analysis with stable prices and altering quantities by quantity-oriented endogenous or exogenous stimuli on the components of intermediate and final demand, or for analysis with stable quantities and changing cost and prices due to cost-push endogenous or exogenous stimuli on the intermediate and the value added productive factors (Pham et al, 2007;Trinh et al, 2012;Choi et al, 2014;Escaith, 2014;Soklis, 2014;Trinh and Phong, 2014;Economakis et al, 2015;H. A. Bekhet et al, 2016;Imansyah et al, 2017;Kolokontes et al, 2018;Mariolis et al, 2018;Muchdie et al, 2018;Kolokontes et al, 2019;Mariolis et al, 2019;Teves, 2019;Ferreira et al, 2020;Han et al, 2020;Kolokontes et al, 2020;Thai et al, 2020;Markaki and Economakis, 2021;Trinh and Thai, 2021).…”
Section: The Positiong Of Adjusted Forward Approach Among the I-o Modelsmentioning
confidence: 99%
“…The next section will analyze Vietnam's import and export situation and their implicationsfor Vietnam's economy. The effects of final demand on output, value added and imports has been studied by M. Muchdie et al (2018) [7], before, in order to explained that imported intermediate input was shown in the usual Keynesian foreign trade multiplier analysis by Trinh et al (2008) [8]. In an open economy, X + M = C + I + E; the external sector is combined inconsistently with the domestic sector in the circular flow.…”
Section: Introductionmentioning
confidence: 99%